Pterigium Pada Penduduk Pesisir Di Nusa Tenggara Barat - Muhammad Amien Rais; Monalisa Nasrul (JUKEJ : Jurnal Kesehatan Jompa, 2022)
Indonesia is an archipelagic country where the majority of the population lives on the coast, causing a high incidence of pterygium. Pterygium is an abnormal growth of tissue in the subconjunctiva of the eye. This is influenced by several factors such as high exposure to sunlight and dry air related to the livelihoods of coastal communities. The diagnosis of pterygium can be seen from the anamnesis, clinical symptoms, and physical examination. Pterygium can be treated through conservative and operative therapy and can be prevented with "TONGKAT WAKTU".